Registration of Land Property Rights Results of Exchange with Village Cash Land through the Complete Systematic Land Registration Program - Dwijayanto, Kurniawan Yoganing; Hanim, Lathifah (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
Complete Systematic Land Registration (PTSL) is a land registration process for the first time, which is carried out simultaneously and covers all land registration objects that have not been registered in a village or sub-district area or other names equivalent to that. Land is not always located in strategic areas. There are several processes including land swaps.The aim of this research is to find out and analyze the process of registering freehold land as a result of an exchange with village treasury land through the PTSL program until the issuance of a freehold certificate in Cilacap district; To find out and analyze the obstacles and solutions faced by the Petitioner, the Regional Government of Cilacap Regency, and the Cilacap Regency Land Office in the Process of Registering Freehold Land as a result of an Exchange with Village Treasury Land through PTSL until the issuance of a Freehold Certificate in Cilacap Regency.In this study, the type of Juridical Sociological research was used, the research specifications were descriptive in nature. The data sources used by the authors were primary data and secondary data. The results of this study areThe process of exchanging community land for village treasury land in Cilacap Regency complies with applicable regulations, namely in accordance with the Letter of the Cilacap Regent dated 22 December 2004 Number: 143/033/00. While the process of registering freehold land as a result of swaps with village treasury land through the PTSL Program in Cilacap Regency is in accordance with the PTSL technical instructions Number 1/Juknis-100.Hk.02.01/I/2021 and has been completed until the issuance of the Freehold Certificate. The Petitioner and the Regional Government in implementing the Registration of Freehold Land as a result of the Exchange with Village Treasury Land through the PTSL Program until the issuance of the Freehold Certificate in Cilacap Regency did not encounter any obstacles. Meanwhile, the obstacle faced by the Cilacap District Land Office is that the distance between the swap process and the very long land registration, which is 18 years, raises obstacles. Keywords: Exchange; Land; Registration; Village.